Seizure recurrence and remission after switching antiepileptic drugs - Wang, Sophia Pan (2012)
PURPOSE: Studies of seizure outcome in patients undergoing serial antiepileptic drug trials have all been uncontrolled, with no account made for the spontaneous changes in disease state that could confound the elucidation of drug effects. In addition, no study has ever looked at outcome following antiepileptic drug switch in seizure-free patients, despite the fact that this is done routinely in clinical practice. We aimed to address both of these issues using a matched case-cohort design. METHODS: We followed patients taking phenytoin or carbamazepine in monotherapy for focal epilepsy who were being crossed over to a newer agent as part of studies on the metabolic effects of anticonvulsant therapy. Many had been seizure-free but were being switched nonetheless due to side effects or concerns about long-term adverse consequences. Each patient was matched with two controls of the same seizure status who were on anticonvulsant monotherapy and whose drug was not switched. Seizure freedom over the ensuing 6 months was the primary endpoint. KEY FINDINGS: There were 43 cases and 86 matched controls. Twenty-three case patients had been seizure-free on their old drug; 5 (21.7%) had seizure recurrence after drug switch compared to 2/46 matched controls (4.3%). Twenty case patients were having seizures on their old drug; 6 (30%) entered remission after drug switch, compared to 8/40 matched controls (20%). The two groups differed at baseline in number of anticonvulsants previously failed, which was the most important factor for prognosis. After statistical adjustment to account for this, seizure-free patients had 6.53 times higher odds of seizure recurrence if switched to a new drug (95% CI 1.02 – 61.19; p=0.06). Non-seizure-free patients had 1.66 times higher odds of remission if they remained on the same drug compared to switching, though this was not significant (95% CI 0.36 – 8.42; p=0.532). Neither dose changes, nor drug mechanism, nor duration of seizure-freedom had any bearing upon the results. SIGNIFICANCE: While the large majority of seizure-free patients remain so when switched to another agent, about one-sixth have a recurrence attributable to the change. Conversely, our study design provides the first evidence to suggest that most improvements in drug-resistant patients are likely due to spontaneous remissions, not new drug introductions. These findings have conflicting implications for two competing models of comparative antiepileptic drug efficacy, which will require further study to elaborate.